Translation and Validation of the Revised "Rushton Moral Resilience Scale" in Greek - Aglaia Katsiroumpa; Ioannis Moisoglou; Olympia Konstantakopoulou; Theodosia Tapaskou; Parisis Gallos; Maria Tsiachri and Petros Galanis (Professor Despina Sapountzi-Krepia, 2024)
Translation and Validation of the Revised "Rushton Moral Resilience Scale" in Greek